Immunity from Seizure and Suit in Australia: The Protection of Cultural Objects on Loan Act 2013. Issue 2 (26th June 2014) - Forrest, Craig
Abstract: Australia has, like many other states over the past few years, introduced a statute that provides immunity from seizure for cultural objects on loan from abroad and immunity from suit for certain parties. This article explores the historical context that lead to the adoption of this statute and comprehensively explores the legislative regime, highlighting its peculiarities.